2023
DOI: 10.1177/09603271231193392
|View full text |Cite
|
Sign up to set email alerts
|

Role of hypoxia inducible factor/vascular endothelial growth factor/endothelial nitric oxide synthase signaling pathway in mediating the cardioprotective effect of dapagliflozin in cyclophosphamide-induced cardiotoxicity

Abstract: Background Cyclophosphamide (CP) is a commonly used chemotherapeutic and immunosuppressive alkylating agent. However, cardiac adverse effects of CP interfere with its clinical benefit. Cardio-oncology research is currently an important issue and finding effective cardiopreserving agents is a critical need. For the first time, we aimed to detect if dapagliflozin (DAP) could ameliorate CP-induced cardiac injury and investigated the role of hypoxia inducible factor α (HIF1α)/vascular endothelial growth factor (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Notably, we found that SGLT2 expression was higher in LSECs than in hepatocytes or Ac-hHSCs, and its expression increased as capillarization progressed. SGLT2 is mainly expressed in the renal proximal tubules, but many studies have recently revealed SGLT2 expression in vascular endothelial cells, as evidenced by the cardiovascular protective effects of SGLT2-Is [ 16 , 21 , 34 ]. Thus, it is possible that tofogliflozin predominantly affected capillaries in hLSECs through SGLT2 in the cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we found that SGLT2 expression was higher in LSECs than in hepatocytes or Ac-hHSCs, and its expression increased as capillarization progressed. SGLT2 is mainly expressed in the renal proximal tubules, but many studies have recently revealed SGLT2 expression in vascular endothelial cells, as evidenced by the cardiovascular protective effects of SGLT2-Is [ 16 , 21 , 34 ]. Thus, it is possible that tofogliflozin predominantly affected capillaries in hLSECs through SGLT2 in the cirrhotic liver.…”
Section: Discussionmentioning
confidence: 99%
“…Recent case reports have demonstrated that SGLT2-Is reduce ascites and peripheral edema in patients with liver cirrhosis, which can be attributed to their action on endothelial cells [ 18 ]. Several studies have shown that SGLT2-Is can directly affect endothelial function independently of glycemic status and through various pathways, resulting in improved vasodilation via increased NO production and bioavailability [ 19 , 20 , 21 ]. Moreover, SGLT2-Is also repressed ET-1 expression while enhancing eNOS activation in a mouse myocardial ischemia–reperfusion injury model [ 22 ].…”
Section: Introductionmentioning
confidence: 99%